Wheezing Is Common in Children With Sickle Cell Disease When Compared With Controls. Issue 1 (January 2015) - Galadanci, Najibah A.; Liang, Wayne H.; Galadanci, Aisha A.; Aliyu, Muktar H.; Jibir, Binta W.; Karaye, Ibraheem M.; Inusa, Baba P.; Vermund, Sten H.; Strunk, Robert C.; DeBaun, Michael R.
<x xml:space="preserve">Abstract</x> In children with sickle cell disease (SCD), wheezing may occur in the absence of asthma. However, the prevalence of wheezing in children with SCD when compared with children without SCD (controls) in the same setting is unknown. Using a case-control study design, we tested the hypothesis that children with SCD would have a higher rate of wheezing than those without SCD. We enrolled 163 children with SCD (cases) and 96 children without SCD (controls) from a community hospital in Nigeria. Parent reports of respiratory symptoms were identified based on responses to questions taken from the American Thoracic Society Division of Lung Diseases' Questionnaire. The median age was 8.5 years for children with SCD and 7.7 years for controls. Cases were more likely than controls to report wheezing both with colds (17.3% vs. 2.1%, P<0.01) and without colds (4.9% vs. 0%, P=0.03). Cases had 9.8 times greater odds of wheezing (95% confidence interval, 2.3-42.2). In the multivariable model, the only variable associated with wheezing was SCD status (odds ratio=18.7, 95% confidence interval, 2.5-142; P=0.005). Children with SCD experience a significantly higher rate of wheezing when compared with children of similar age without SCD.